Sustainability Risks and Supply Chain Dynamics Strategies in Vietnam's FMCG Industry - Anh, Nguyen Ngoc Quynh (Digital Repository of Theses, 2026)
Recent rapid changes in supply chains, such as the COVID-19 pandemic, globalization, the development of information technology, and the trend of outsourcing software and manufacturing, have made supply networks much more complex, especially in terms of sustainability. This increases the vulnerability and fragility of supply chains to sustainability-related risks, making supply chain risk management a crucial and challenging issue, particularly in the sensitive and volatile FMCG sector in Vietnam. The author conducted theoretical research, synthesized appropriate measurement scales, and studied over 250 companies to develop a comprehensive scale for assessing sustainability risks in supply chains and empirically verified the impact of these risks on suppliers, customers, and the economic performance of businesses. In addition, the study will also evaluate the effectiveness of dynamic supply chain management techniques in addressing the impact of sustainability-related risks on business performance characteristics. The results found that three groups of SSCRs—Macro-economic Risks, Customer Demand Risks, and Supplier Risks—all have a negative impact on SCP. This finding aligns with the characteristics of the Vietnamese market, which is considered immature and highly sensitive to price. Finally, the study rejected the moderating role of Supply Chain Risk Management (SCRM) practices on the negative relationship between SSCRs and SCP. However, the SCRM strategies were proven to have a positive direct impact on SCP. These findings provide several theoretical and managerial implications for managers in addressing the economic, social, and environmental issues associated with sustainable supply chain risks.